State Institutional Law: The DSN-MUI Institution and its Role in Preventing Sharia Disputes - Muhammad Ali Hanafiah Selian; Nur Rohim Yunus; Abdurrauf Abdurrauf (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
This article's goal is to explain how the National Sharia Council Institution - Indonesian Ulema Council (DSN-MUI) works to avoid sharia conflicts. The purpose of this research is to provide a holistic view of the DSN-MUI's role in settling potential disputes involving sharia-related components of different spheres of life. This article uses a qualitative research method with a literature approach, meaning that it takes information from previously published works at the DSN-MUI Institute and the role it plays. The information collected is then critically examined to reveal how the DSN-MUI can be used to avoid and resolve sharia-based legal problems. The findings of the study indicate that the DSN-MUI Institute plays a significant part in the avoidance of sharia disagreements by issuing fatwas and guidance. Because the DSN-MUI acts as a respected authority in interpreting Islamic law and offering guidance on its application, it is able to avoid or resolve a variety of possible issues that may develop as a result of differences in the interpretations of Islamic law. In addition, the DSN-MUI serves as a community-recognized organization for the resolution of disputes, thereby assisting in the prevention of conflicts and the discovery of solutions that are in conformity with the tenets of sharia law.Keywords: DSN-MUI; Sharia Disputes; The Role of Prevention Abstrak:Artikel ini bertujuan untuk menjelaskan bagaimana Lembaga Dewan Syariah Nasional - Majelis Ulama Indonesia (DSN-MUI) bekerja untuk menghindari konflik syariah. Tujuan dari penelitian ini adalah untuk memberikan pandangan holistik tentang peran DSN-MUI dalam penyelesaian potensi sengketa yang melibatkan komponen-komponen yang terkait dengan syariah dari berbagai bidang kehidupan. Artikel ini menggunakan metode penelitian kualitatif dengan pendekatan literatur, artinya mengambil informasi dari karya-karya yang diterbitkan sebelumnya di Institut DSN-MUI dan peran yang dimainkannya. Informasi yang terkumpul kemudian dikaji secara kritis untuk mengungkap bagaimana DSN-MUI dapat digunakan untuk menghindari dan menyelesaikan permasalahan hukum berbasis syariah. Temuan penelitian menunjukkan bahwa DSN-MUI Institute berperan penting dalam menghindari perselisihan syariah dengan mengeluarkan fatwa dan tuntunan. Karena DSN-MUI bertindak sebagai otoritas yang dihormati dalam menafsirkan hukum Islam dan menawarkan pedoman penerapannya, ia mampu menghindari atau menyelesaikan berbagai kemungkinan masalah yang mungkin berkembang sebagai akibat dari perbedaan interpretasi hukum Islam. Selain itu, DSN-MUI berfungsi sebagai organisasi penyelesaian sengketa yang diakui masyarakat, sehingga membantu pencegahan konflik dan penemuan solusi yang sesuai dengan prinsip hukum syariah.Kata Kunci: DSN-MUI; Sengketa Syariah; Peran Pencegahan